Cilia‐Mediated Insulin/Akt and ST2/JNK Signaling Pathways Regulate the Recovery of Muscle Injury. Issue 1 (14th November 2022) - Yamakawa, Daishi; Tsuboi, Junya; Kasahara, Kousuke; Matsuda, Chise; Nishimura, Yuhei; Kodama, Tatsuya; Katayama, Naoyuki; Watanabe, Masatoshi; Inagaki, Masaki
Abstract: Following injury, skeletal muscle regenerates but fatty tissue accumulation is seen in aged muscle or muscular dystrophies. Fibro/adipogenic progenitors (FAPs) are key players in these events; however, the effect of primary cilia on FAPs remains unclear. Here, it is reported that genetic ablation of trichoplein (TCHP), a ciliary regulator, induces ciliary elongation on FAPs after injury, which promotes muscle regeneration while inhibiting adipogenesis. The defective adipogenic differentiation of FAPs is attributed to dysfunction of cilia‐dependent lipid raft dynamics, which is critical for insulin/Akt signaling. It is also found that interleukin (IL) 13 is substantially produced by intramuscular FAPs, which are upregulated by ciliary elongation and contribute to regeneration. Mechanistically, upon injury, long cilia excessively activate the IL33/ST2/JNK axis to enhance IL13 production, facilitating myoblast proliferation and M2 macrophage polarization. The results indicate that FAPs organize the regenerative responses to skeletal muscle injury via cilia‐mediated insulin/Akt and ST2/JNK signaling pathways. Abstract : Skeletal muscle regeneration requires functional crosstalk between muscle cells and fibro/adipogenic progenitors (FAPs). In this article, it is shown that primary ciliary elongation on FAPs suppresses intramuscular adipogenesis after muscle injury by disturbing lipid raft‐dependent insulin/Akt signaling and also contributes to muscle regeneration by promoting myoblast proliferation and M2 macrophage infiltration via IL33/ST2/JNK pathway‐dependent IL13 production.